Guided Internet-delivered cognitive behaviour therapy for perfectionism in a non-clinical sample of adolescents: A study protocol for a randomised controlled trial - Jones, Emily J.; Howell, Jennifer; Tonta, Kate; Egan, Sarah; Hasking, Penelope; Boyes, Mark; McEvoy, Peter; Mazzucchelli, Trevor (ELSEVIER, 2020)
Background: Perfectionism is elevated across a range of psychopathologies and has been shown to impede treatment outcomes. There is also evidence suggesting elevated perfectionism may contribute to the onset and maintenance of non-suicidal self-injury. There is a growing body of evidence suggesting that Internet-delivered cognitive-behavioural therapy for perfectionism reduces perfectionism and symptoms of psychological disorders and that reductions are maintained at 3-month and 6-month follow-up. There may also be reductions in non-suicidal self-injury, although no study has investigated this potential benefit. Given that associations between perfectionism and psychopathology are observed across both adults and adolescents, the need for the development of interventions targeting adolescents is essential for early intervention and prevention. Methods: The present study will employ a randomised controlled trial to examine the efficacy of 8-week guided Internet-delivered cognitive-behavioural therapy for perfectionism in adolescents compared to a waitlist control group. The primary outcome is perfectionism, and secondary outcomes include symptoms of psychological disorders, well-being, and non-suicidal self-injury. Outcomes will be assessed at pre-intervention, post-intervention, 1-month follow-up, 3-month follow-up, and 6-month follow-up. A minimum of 240 participants will be recruited online through social media, Australian universities, and schools across Australia. Generalised linear mixed models will be used to test for changes in outcomes between the intervention group and the waitlist control. Discussion: The outcomes of this trial will contribute to the literature on perfectionism and psychopathology in adolescents, as well as the efficacy of guided Internet-delivered interventions for adolescents. Trial registration: The trial was registered on the 20th of June 2019 at the Australia New Zealand Clinical Trials Registry (ACTRN12619000881134). Trial status: This is protocol version 1.0. Participant recruitment began on 31 July 2019 and is still actively running with an anticipated completion date in the fourth quarter of 2020.